2018
DOI: 10.1182/blood-2018-03-840132
|View full text |Cite|
|
Sign up to set email alerts
|

Identification of novel mutational drivers reveals oncogene dependencies in multiple myeloma

Abstract: Understanding the profile of oncogene and tumor suppressor gene mutations with their interactions and impact on the prognosis of multiple myeloma (MM) can improve the definition of disease subsets and identify pathways important in disease pathobiology. Using integrated genomics of 1273 newly diagnosed patients with MM, we identified 63 driver genes, some of which are novel, including ,, ,, and Oncogene mutations are significantly more clonal than tumor suppressor mutations, indicating they may exert a bigger … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
507
0
9

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
2

Relationship

4
5

Authors

Journals

citations
Cited by 381 publications
(543 citation statements)
references
References 54 publications
27
507
0
9
Order By: Relevance
“…Data analysis was performed as described previously, with minor differences between sequencing modalities. 32 For details see Supplementary Methods.…”
Section: Resultsmentioning
confidence: 99%
“…Data analysis was performed as described previously, with minor differences between sequencing modalities. 32 For details see Supplementary Methods.…”
Section: Resultsmentioning
confidence: 99%
“…This strong association was likely missed in earlier studies given that PHF19 expression is not associated with any cytogenetic feature while several therapeutic advances over the last 20 years have made it difficult to model outcome across multiple studies from different periods. Furthermore, PHF19 has not been found to be significantly mutated in sequencing-based studies 28,29 , suggesting that its overexpression is not directly related to genomic alterations within the PHF19 gene. We also show that a simple four feature predictor composed of age, ISS, and expression of PHF19 and MMSET performs similarly to more complex models with many more gene expression features included (Supplemental Figure 4).…”
Section: Discussionmentioning
confidence: 98%
“…MM is a unique case study of Ras biology as approximately 40% of MM patient tumors have predicted activating mutations in KRAS or NRAS 4,5 , with an almost equal distribution between the two, but essentially none in HRAS. Notably, these KRAS and NRAS mutations are very rare in the precursor lesion monoclonal gammopathy of uncertain significance (MGUS), suggesting that RAS mutations are important for transformation to MM 16 .…”
Section: Introductionmentioning
confidence: 99%
“…In vitro overexpression studies in myeloma cell lines indicated that KRAS may lead to more rapid proliferation in the absence of interleukin-6 (IL-6) stimulation than NRAS 20,21 . More recent sequencing studies have suggested that NRAS mutations tend to cluster with specific genomic aberrations in MM 5 . Finally, immunohistochemistry studies on MM bone marrow have suggested possible differences in ERK phosphorylation depending on RAS isoform and specific mutation 22 .…”
Section: Introductionmentioning
confidence: 99%